ABNORMALITAS TOKOH DALAM COSMÉTIQUE DE L'ENNEMI KARYA AMÉLIE NOTHOMB - Yodhia Kinriabe, Farah; Yolanda Latjuba, Ade; Hasyim, Muhammad (JURNAL ILMU BUDAYA, 2023)
The object that used for this research tells about the interaction between two men who initially didn't know each other. They were stuck in a flight delay at the airport. The two men talked about many things. And then the facts were revealed, one of them had extreme hallucinations and the other was the part of the man who had the hallucinations. This research aims to explain what kind of abnormal behavior the character has and explain the relationship between events that occur in the character's life and his abnormal behavior. The theories used for this analysis are characterization, psychology of literature, abnormal psychology, and events. The results of this research indicate that the two main characters have abnormal behavior in the form of behavior that violates social norms, maladaptive behavior, hallucinations, and dangerous behavior.